Return on investment of health intervention among diabetic patient: A systematic review - Ida Krisnadewi Kadek; Ari Kristina Susi; Endarti Dwi; Murti Andayani Tri (BIO Web of Conferences, 2023)
A strategy for reducing healthcare costs of diabetic mellitus (DM) is by reducingbody weight and blood glucose through lifestyle-modification programs such as intensive lifestyle interventions, mealreplacement programs, and physical activity. A return on investment (ROI) analysis needs to be done to see a program’s effectiveness, which aims to make this program provide benefits, especially in the long term. In this systematic review, the authors describe ROI, the program, the program’s cost, adoption, and implementation. The authors searched the Science Direct, Pubmed, and SAGE databases using the following search terms: ‘Return on Investment’ AND ‘DiabeticMellitus’ and Programs”. Moreover, hand searching identifies further studies. This review includes eight articles, and most articles on lifestyle modification intervention have great ROI; several articles with public health workers have great ROI. The findings show that long-term and program intensity in a long time horizon plays a major role in outcomes and more significant ROI. Programs with lifestyle intervention fellow health workers or CHWs that helped deliver physical activity, education, and dietary had a good impact in lowering diabetes risk.